Desensitizing effects of violent on media bullying. - Anasis, Anna Marie Camilet
The study examined the links between repeated exposure to violent media stimuli and desensitization to violence as a predictor variable and bullying tendency as outcome variables. Participants in two different conditions were made to watch a different set of video clips for three consecutive days. Experimental groups were made to watch violent video clips, and for control group, nonviolent video clips. Following the clip, participants for both group completed a Positive and Negative Affect Schedule to measure desensitization and Tendency to Bully Scale to measure the tendency of the participants to bully. One-way analysis of variance and test of means were used to determine whether there are significant differences between sessions and between groups. The result showed significant results across variables except for the positive affect on the last session. Repeated exposure to violent video clips was found to increase experimental participants positive affect, decrease negative affect and increase the tendency to bully. Speculations were drawn from these results.